Preparation methods and performance of new tungsten-based ceramic alloy. (August 2021) - Fu, Jianping; Ren, Kai; Yin, Likui; Yang, Rui; Zhao, Taiyong; Chen, Zhigang
Graphical abstract: Highlights: TCA is a new alloy consisting of an alloy matrix and Al2 O3 ceramic microspheres. Analysis: microstructure, mechanical properties, high speed penetration. The influence of ceramic microspheres content on TCA was analyzed by DOP test. Abstract: In this study, a new tungsten-based ceramic alloy (TCA) is obtained using liquid-phase sintering during the preparation of traditional 95 W alloys. In this process, sintered Al2 O3 ceramic microspheres with a purity of 99%, a mass fraction of 1% ~ 5%, and the particle size of 60 ~ 120 μm are added. This new material's microstructure, mechanical properties, fracture mechanism, and high-speed penetration performance are studied. Results show that the TCA's tensile strength, ductility, and impact toughness decrease with the addition of Al2 O3 ceramic. However, when 3 wt% Al2 O3 ceramic is added, the TCA spherical fragment exhibits the best high-speed impact property against the 616 rolled homogeneous armor plate (22SiMn2TiB) of 15 mm thick. Therefore, TCA can be used as the material of the kinetic energy damage element to improve its high-speed penetration ability.